Rule Based Fuzzy Indexing for Grading of proposed Industrial Sites for Power Plant Installation (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The problem of site selection in an indefinite environment has gained overriding importance in recent years. In case of selection of a site for the construction of new hazardous power plants have attained significance due to a variety of reasons. The authors believe that the issue of site selection for an upcoming, say, a power plant installation based only on Environmental impact assessment (EIA) study could be inadequate. Therefore, there is a need to look beyond EIA process, and suggest poilcy makers a set of useful mathematical techniues with an objective to rank the sites for such installtions. EIA is aimed at identifying the possible impacts of Industrial development activities on the existing Environment. This method begins with initial screening to check if it may result in negative impacts on the Environment. Scoping determines which components to include in the initial screening phase. Many components considered in the process cannot be measured precisely (e.g., response to public involvement programs, willingness for resettlement, possible effects on economy, social acceptance etc.,). In order to process this vague and subjective information, we have applied Fuzzy Indexing with a Rule base to check the suitability of a site for Thermal, Hydroelectric, Nuclear and Gas based Power Plant installations and classify them as v. Good, ˜Good, ˜Fair and Poor and finally grade them.